The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/rhu.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Predictors of Communication About High Blood Pressure in Rheumatoid Arthritis Visits

Abstract: Regardless of BP magnitude, most RA clinic visits lacked documented communication about BP despite compounded CVD risk. Future work should study how rheumatology clinics can facilitate follow-up of high BPs to address HTN as the most common and reversible CVD risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…High blood pressure (BP) is the most prevalent and reversible cardiovascular disease (CVD) risk factor among all adults, (1) with even higher risk in rheumatology patients like those with rheumatoid arthritis (RA). (2, 3) Still, we reported that only 10% of eligible RA visits recommended follow-up of high BP (4) and that RA patients were less likely to have their hypertension diagnosed than peers meeting identical longitudinal BP thresholds. (5) Treating high BP in 11 at-risk patients could prevent one CVD event, (6) yet half of US adults with hypertension lack BP control.…”
Section: Conclusion-implementing the Bp Connect Specialty Clinic Protocol In Rheumatology Clinicsmentioning
confidence: 91%
“…High blood pressure (BP) is the most prevalent and reversible cardiovascular disease (CVD) risk factor among all adults, (1) with even higher risk in rheumatology patients like those with rheumatoid arthritis (RA). (2, 3) Still, we reported that only 10% of eligible RA visits recommended follow-up of high BP (4) and that RA patients were less likely to have their hypertension diagnosed than peers meeting identical longitudinal BP thresholds. (5) Treating high BP in 11 at-risk patients could prevent one CVD event, (6) yet half of US adults with hypertension lack BP control.…”
Section: Conclusion-implementing the Bp Connect Specialty Clinic Protocol In Rheumatology Clinicsmentioning
confidence: 91%
“…All patients were ≥20 years old and seen regularly for primary and rheumatology care (≥2 health system visits with at least one primary care visit in 24 months) and had rheumatology clinic notes clearly documenting rheumatoid arthritis in the absence of another specific inflammatory arthritis diagnosis (Figure 1). One cohort included RA patients with prevalent hypertension [12] according to Electronic Health Record (EHR) algorithms using the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC-7) [13]. The second cohort included patients who were eligible for cholesterol screening or control [14, 15].…”
Section: Methodsmentioning
confidence: 99%
“…This is well illustrated in the area of cardiovascular disease (CVD) prevention, where clinic protocols executed by medical assistants have improved the proportion of primary care clinic patients whose blood pressure (BP) is controlled from 50 to > 80% [ 8 ]. In specialty clinics, however, clinicians discuss CVD risk factors such as BP or tobacco in only 10% of relevant specialty visits, despite routinely assessing them [ 9 , 10 ]. Non-vascular specialty clinics have not implemented protocols to address high BP and tobacco use, which are the most prevalent risk factors for CVD in US adults.…”
Section: Introductionmentioning
confidence: 99%